The Verstek Law Implementation In Religious Courts In South Sumatera - Insani, Fidya Rahma; Hayatuddin, Khalisah; Saptawan, Ardiyan; Is, Muhamad Sadi (Universitas Islam Negeri Raden Fatah Palembang, 2023)
Verstek decisions are decisions that often occur in courts, especially in the Religious Courts, so the authors were interested in conducting them by using the formulation of the problem: how to apply verstek at Sekayu Religious Courts, South Sumatra. Then, what are the obstacles in implementing verstek at Sekayu Religious Court, South Sumatra. Empirical research was used as the method of research. Research result; the application of verstek at Sekayu Religious Court of South Sumatra has been carried out in accordance with applicable law. Meanwhile, the obstacles faced by the Sekayu Religious Court of South Sumatra in resolving the verstek case were; the number of divorce cases was quite high from year to year; the time required in handling takes a long time, from the beginning of registration until the decision was read out; the down-payment fee for the verstek case had been determined by the Religious Court based on the radius of residence of the applicant/plaintiff and the respondent/defendant, not adjusted to the financial capacity of the parties; and witness constraints, sometimes the parties present witnesses who had never seen or heard of the dispute, but indeed the husband and wife had been separated for a long time.